MRNA translation from an antigen presentation perspective: A tribute to the works of Nilabh Shastri. (January 2022) - Apcher, Sebastien; Tovar-Fernadez, Maria; Ducellier, Sarah; Thermou, Aikaterini; Nascimento, Megane; Sroka, Ewa; Fahraeus, Robin
Highlights: Alternative mRNA translation initiation plays a key role in the immune system's capacity to distinguish self from non-self. Peptide substrates for the MHC class I pathway are produced by non-canonical mRNA translation. MHC I peptides substrates are encoded from non-canonical reading frames. Abstract: The field of mRNA translation has witnessed an impressive expansion in the last decade. The once standard model of translation initiation has undergone, and is still undergoing, a major overhaul, partly due to more recent technical advancements detailing, for example, initiation at non-AUG codons. However, some of the pioneering works in this area have come from immunology and more precisely from the field of antigen presentation to the major histocompatibility class I (MHC-I) pathway. Despite early innovative studies from the lab of Nilabh Shastri demonstrating alternative mRNA translation initiation as a source for MHC-I peptide substrates, the mRNA translation field did not include these into their models. It was not until the introduction of the ribo-sequence technique that the extent of non-canonical translation initiation became widely acknowledged. The detection of peptides on MHC-I molecules by CD8 + T cells is extremely sensitive, making this a superior model system for studying alternative mRNA translation initiation from specific mRNAs. In view of this, we give a brief history on alternative initiation from an immunology perspective and its fundamental role in allowing the immune system to distinguish self from non-self and at the same time pay tribute to the works of Nilabh Shastri.